Systematic review and meta-analysis of women's awareness of obstetric fistula and its determinants in Ethiopia - Melis, Tamirat; Mose, Ayenew (Frontiers in Global Women's Health, 2023)
Although obstetric fistula was virtually eliminated in developed countries due to comprehensive obstetric health care services, in developing countries including Ethiopia many women and girls are still silently suffering from obstetric fistula due to early marriage, poor socioeconomic status, lack of access to the skilled birth attendant, and limited awareness of obstetric fistula. Objective: - To estimate the pooled prevalence of women’s awareness of obstetric fistula and its associated factors in Ethiopia. Methods We strictly followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to conduct this study. We used visual inspection of the symmetry in the Funnel plot and Eggers test to assess publication bias. Cochrane Q-test and I2 statistic were done to check evidence of heterogeneity between the studies. Data were extracted using a Microsoft Excel spread sheet and analysed using STATA version 14 statistical software. Results A total of 6 studies with 3,024 women’s were included. The pooled prevalence of women awareness of obstetric fistula in Ethiopia was 41.24% (95%CI; 32.94%-49.54%). Urban residence (AOR=2.32, 95% CI; 1.40-3.85), giving birth at a health institution (AOR=2.84, 95% CI; 1.92-4.21) having secondary and above educational status (AOR=3.27, 95% CI; 2.15-4.97), having antenatal care follow up (AOR=2.73, 95% CI; 1.71-4.35), and participated in pregnant women conference (AOR=4.64, 95% CI; 2.88-7.49) were factors associated with good awareness of women’s about obstetric fistula in Ethiopia. Conclusion The pooled prevalence of women’s awareness of obstetric fistula was low. Urban residence, giving birth at a health institution, having secondary and above educational status, having antenatal care follow up, and participating in pregnant women conference were factors associated with women’s awareness of obstetric fistula. Therefore, enhancing women’s awareness on obstetric fistula, promoting institutional delivery, and antenatal follow-up was recommended. Furthermore, policymakers and stakeholders should empower women and provide special attention to a neglected but most important public health problem such as obstetric fistula.